Open: Effects of NGM282, an FGF19 variant, on colonic transit and bowel function in functional constipation: a randomized phase 2 trial. (May 2018) - Oduyebo, Ibironke; Camilleri, Michael; Nelson, Alfred D.; Khemani, Disha; Nord, Sara Linker; Busciglio, Irene; Burton, Duane; Rhoten, Deborah; Ryks, Michael; Carlson, Paula; Donato, Leslie; Lueke, Alan; et al.
Abstract : OBJECTIVE: NGM282 is an analog of fibroblast growth factor 19 (FGF19), a potent inhibitor of bile acid (BA) synthesis in animals and humans. In phase 2 trials in type 2 diabetes and primary biliary cholangitis, NGM282 was associated with dose‐related abdominal cramping and diarrhea. We aimed to examine effects of NGM282 on colonic transit, stool frequency and consistency, hepatic BA synthesis (fasting serum C4), fecal fat, and BA in functional constipation (FC). METHODS: Two‐dose NGM282 (1 and 6 mg, subcutaneously daily), parallel‐group, randomized, placebocontrolled, 14‐day study in patients with FC (Rome III criteria) and baseline colonic transit 24 h geometric center (GC) <3.0. We explored treatment interaction with SNPs in genes KLB, FGFR4, and TGR5 ( GPBAR1 ). Statistical analysis: overall ANCOVA at α = 0.025 (baseline as covariate where available), with three pairwise comparisons among the three groups ( α = 0.008). RESULTS: Overall, NGM282 altered bowel function (number of bowel movements, looser stool form, and increased ease of passage) and significantly accelerated gastric and colonic transit. Dose‐related effects were seen with GC 24 h, but not with gastric emptying (GE) and GC 48 h. There were no differences in fecal fat or weight, but there was reduced fecal total BA excretion with NGM282. The most common adverse events were increased appetite ( n = 0 with placebo, 2 with 1 mg, 9 with 6 mg), injection site reaction ( n = 2 placebo, 4 with 1 mg, 8 with 6 mg), and diarrhea ( n = 1 with 1 mg and 4 with 6 mg NGM282). There was treatment interaction with KLB SNP, with greater increase in colonic transit in participants with the minor A allele ( p = 0.056). CONCLUSION: NGM282 significantly impacts GE and colonic transit, consistent with the observed clinical symptoms. The specific mechanism of prokinetic activity requires further research.